A technoeconomic risk assessment of aero-gas turbine engine upgrades. - Igbong, Dodeye Ina (Cranfield University, 2018)
Many, especially smaller operators, lack the analytical tools to carry out an effective cost-benefit analysis for upgrades they may be offered. The research aims to fill this gap and develop a methodology to carry out an effective quantitative evaluation of the performance, economics and risk outcomes and alternative uses of upgrade using the TERA (Techno-economic Environmental and Risk Assessment) framework. The decision whether or not to adopt an engine upgrade is usually based on the cost-benefit and risk evaluation of the upgrade. For these non-mandatory upgrades/modifications or retrofits, the operator adapts its policy regarding estimation of the upgrade benefits relative to its unique operating environment, business models and cost structures. A handful of engine upgrade programmes exist in public literature with different methods of evaluating whether or not to adopt the engine upgrade for investment. The advantage this propose TERA – upgrade methodology has over the conventional methods is its ability to evaluate the engine upgrade from a multidisciplinary (performance, environmental, risk and economic) perspective. The method was developed by the careful adaptation and assembly of a collection of a wide range of technical models, and offers opportunity and adaptability for evaluating both current and novel engines, while reflecting the engine operating conditions and economic realities. Three engine upgrade case studies were evaluated from both the aircraft operator’s perspective and the manufacturer’s perspective. There are; the thermal barrier coating (TBC), increase engine fan diameter and aircraft re-engine upgrades. Results were simulated through the adaptation of three main tools namely TURBOMATCH, HERMES and HESTIA, all of which are developed in Cranfield University, for gas turbine engine performance modelling, aircraft mission performance, maintenance costs, direct operating costs and time between overhaul prediction. Results for TBC upgrade on CEUP56 engine show that a life extension of 36.5% is possible with a 1.08W/mK Ktbc-value relative to baseline. In alternative use, a take-off thrust improvement of 33.32% is predicted delivering a payload increase of 3485kg, or a runway length reduction of 14% assuming a constant cooling flow scenario. The small (< 1 inch) increase in fan diameter upgrade deployed on the CEUP6-80 engine delivered a maximum posible improvement of +2.47% and -0.436% in thrust and fuel burn savings relative to baseline, respectively. Re-engining upgrade of existing aircraft yielded engine SFC reduction of 9.5% and aircraft block fuel burn savings of up to 9.2% relative to baseline. The economics of these upgrades were evaluated on a cost-benefit anlysis basis and the potential investment NPV estimated. Results obtained show significant performance and economic benefits to merit investment in aero-engine upgrade project for all case study considered. The benefits of the methodology as a decision support tool is derived from the compelling relevance of this work embodied in the consistent approach to reveal informed insights on the performance and economics of each upgrade technology within a variety of operational space.
Keywords: Aero-engine upgrades; performance and economic improvement; net present value; techno-economic environmental and risk assessment (TERA); novel engines; turbomatch; hermes; hestia